MAKNA PASEPPI’ BOTTING DALAM MASYARAKAT PADA ADAT PERKAWINAN BUGIS DI KABUPATEN SOPPENG - Andi Rahmawakiyah; Tasrifin Tahara; Safriadi Safriadi; Munsi Lampe; Yahya Yahya (Phinisi Integration Review, 2023)
This research was conducted to find out (1) the role of paseppi' botting in Bugis wedding customs in Watansoppeng, (2) The meaning of paseppi' botting in wedding customs in Watansoppeng, the approach used in this research is descriptive qualitative with observational data collection methods, interviews , and documentation then analyze the data with data reduction techniques, data presentation and drawing conclusions.The results of the study show that (1) the role of paseppi' as a symbol of startification which is symbolized in the number of passeppi, namely: One pair of bali botting, comes from the ata' or to sama' class of ordinary people. Two pairs of passeppi botting, are in the aristocratic class which are categorized as bau, andi, petta. Three pairs of passeppi botting belong to the high aristocratic class which are categorized as kings, datu. (2) The people of Soppeng interpret passeppi botting in marriage: a positive impression because paseppi is interpreted as respecting and guiding, accompanying the happiness of a married couple who have made their solemnization of a marriage. Negative impression because many people mix up wedding customs that are not in accordance with their social status.Penelitian ini dilakukan untuk mengetahui (1) peran paseppi’ botting dalam adat perkawinan Bugis di Watansoppeng, (2) Makna paseppi’ botting dalam adat perkawinan di Watansoppeng, pendekatan yang digunakan dalam penelitian ini adalah deskriptif  kualitatif  dengan metode pengumpulan data observasi, wawancara, dan dokumentasi kemudian menganalisis data dengan teknik reduksi data,penyajian data dan penarikan kesimpulan.Hasil penelitian menunjukkan bahwa (1) peran paseppi’ sebagai simbol startifikasi yang dilmbangkan dalam jumlah passeppi yakni : Satu pasang bali botting, berasal dari golongan ata’ atau to sama’ orang biasa. Dua pasang passeppi botting, berada pada golongan bangsawan yang dikategorikan bau, andi, petta. Tiga pasang passeppi botting, berada pada golongan bangsawan tinggi yang dikategorikan sebagai raja, datu.(2) masyarakat Soppeng memaknai passeppi botting dalam perkawinan: kesan positif karena paseppi dimaknai menghargai dan menuntun, mengiringi kebahagiaan suatu pasangan suami istri ini yang telah melakukan ijab Kabul.Kesan negatif karna banyak orang yang mencampur adukkan adat pernikahan yang tidak sesuai dengan status sosialnya.